2018
DOI: 10.1088/1755-1315/125/1/012217
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron parameters in liver cirrhosis

Abstract: Abstract. The liver plays a fundamental role in iron homeostasis. Iron parameters change, especially ferritin, need to be evaluated in patients with liver cirrhosis. Serum ferritin could predict the prognosis of patients with decompensated cirrhosis since it reflects immunemediated and infectious stimuli. Ferritin could express the severity of liver disease and possible subsequent complications. Finally, it might reflect an iron overload condition resulting in significant morbidity and early mortality. 70 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
2
5
1
Order By: Relevance
“…The results of the present study confirm those of Siregar and Maail (2018) who found an increase in hepatic iron accumulation and iron related serum markers elevation. In the current study, the reduction in serum TIBC may be one of the causative factors of serum iron loading.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the present study confirm those of Siregar and Maail (2018) who found an increase in hepatic iron accumulation and iron related serum markers elevation. In the current study, the reduction in serum TIBC may be one of the causative factors of serum iron loading.…”
Section: Discussionsupporting
confidence: 92%
“…Such decrease can leave ionized iron to be available for excessive production of free radicals with subsequent formation of oxidative stress, DNA modification and initiation of hepatocarcinogenesis. (Siregar and Maail, 2018;Shibutani et al, 1991). Therefore, one can suggest that iron loading and oxidative stress can also participate in reduction of hepcidin as was reported by Castagna et al (2010) who also suggested that HCV infection in animal and in cellular models may directly modulate hepcidin expression via HCV-induced reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations